Environmental disinfection with photocatalyst as an adjunctive measure to control transmission of methicillin-resistant Staphylococcus aureus: a prospective cohort study in a high-incidence setting - Min Hyung Kim; Seong Gyu Lee; Ki Sook Kim; Yoon Ji Heo; Ji Eun Oh; Su Jin Jeong (BMC Infectious Diseases, 2018)
Abstract Background Environmental disinfection with continuously antimicrobial surfaces could offer superior control of surface bioburden. We sought to decide the efficacy of photocatalyst antimicrobial coating in reducing methicillin-resistant Staphylococcus aureus (MRSA) acquisition in high incidence setting. Methods We performed prospective cohort study involving patients hospitalized in medical intensive care unit. A titanium dioxide-based photocatalyst was coated on high touch surfaces and walls. Five months of pre-intervention data were compared with five months of post-intervention data. The incidence rates of multidrug-resistant organism acquisition and the rates of hospital-acquired blood stream infection, pneumonia, urinary tract infection, and Clostridium difficile–associated diseases were compared using Cox proportional hazards regression analysis. Results In total, 621 patients were included. There was significant decrease in MRSA acquisition rate after photocatalyst coating (hazard ratio, 0.37; 95% confidence interval, 0.14–0.99; p = 0.04). However, clinical identification of vancomycin-resistant Enterococcus spp. and multidrug-resistant Acinetobacter baumannii did not decrease significantly. The hazard of contracting hospital-acquired pneumonia during the intervention period compared to baseline period was 0.46 (95% confidence interval, 0.23–0.94; p = 0.03). Conclusions In conclusion, MRSA rate was significantly reduced after photocatalyst coating. We provide evidence that photocatalyst disinfection can be an adjunctive measure to control MRSA acquisition in high-incidence settings. Trial registration ISRCTN Registry (ISRCTN31972004). Registered retrospectively on November 19, 2018.